(untitled) (International Journal of Nursing Education, 2024)
Introduction: The inadequate knowledge is the main obstacle of provision of palliative care. This study attempted to examine the association between related factors and knowledge about palliative care for patients with terminal cancer among nursing students in Bangkok, Thailand. Methods: This study was cross-sectional, conducted in June 2024 at Saint Louis College, Bangkok, Thailand. Data were collected through self-administered questionnaires measuring sociodemographic characteristics. We employed the Palliative Care Quiz for Nursing (PCQN) and the Frommelt Attitude Toward Care of the Dying (FATCOD), form B. Descriptive statistics and multiple linear regression were selected to use for analysis. Results: The participants were 111 third-year nursing students. The mean score of knowledge about palliative care for patients with terminal cancer was 8.52 (SD = 1.84. The significant predictors of knowledge about palliative care for patient with terminal cancer were experience of losing close relatives or beloved ones from cancer within 1 year (β = 1.083, p < 0.05), and attitude toward dying (β = 0.041, p < 0.05). Conclusion: This study highlights that nursing students had insufficient palliative care knowledge for patient with end-stage cancer. These findings implies that better attitude toward caring for end-of-life patient associated with improved palliative care knowledge. Therefore, to develop educational program of palliative care for nursing students with psychological and spiritual care training should be embedded in the program for optimum palliative care for patients with terminal cancer.